Manoel de Barros: horizontes pantaneiros em terras estrangeiras - Vieira, Tania Regina (2007)
The aim of this study is to analyze the reception of Manoel de Barros‟s work in foreign lands, focusing on the translation of some of his poems to English, Spanish and French. The object of research is a bilingual photograph album with Barrosian poetry translated into English by João Rache, para encontrar o azul eu uso pássaros/ to find blue I use birds, a Spanish anthology, Todo lo que no invento es falso, translated by Jorge Larrosa, and a French translation of O Livro das Ignorãças entitled La parole sans limite: une didactique de l’invention by Celso Libânio. Poems that were more expressive and representative of the author‟s literary production were selected to discuss the reception of his work abroad. Manoel de Barros was chosen because of the reflective and innovative content of his work, which from regional and telluric themes transcends the Pantanal‟s frontiers to reach universal horizons, allowing the extension of his work to foreign lands. This investigation is based on translation theory, especially on literary translation, and on language studies. The theoretical and critical framework is based on the reflections of Laranjeira, Meschonnic and Riffaterre and on the philosophical hermeneutics of Gadamer. We point out that our purpose is to develop an analysis which permits us to get an insight into Manoel de Barros‟s work to learn more about it and to understand the overall translation process. It is our belief that it is possible to find a meeting point in the diversity of the cultures through translation, enriching and broadening the knowledge of the target reader about the original culture.